2004
DOI: 10.1002/aic.10227
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and water electrolysis effects in electrofiltration of kaolin suspension

Abstract: Filtration combined with an electric field (electrofiltration) enhances the filtration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…In an electric field of proper polarity, electrophoresis reduces the rate of cake formation and increases the rate of permeation through the filter cake by electroosmosis. Various laboratory-scale research results have shown that electrofiltration greatly enhanced the filtration kinetics of aqueous suspensions of anatase [7], quartz sand [8], and kaolin [9]. A similar finding was also obtained in a pilot-scale electrofiltration of SiO 2 using a polyamide membrane with a 0.2-m pore size [10].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In an electric field of proper polarity, electrophoresis reduces the rate of cake formation and increases the rate of permeation through the filter cake by electroosmosis. Various laboratory-scale research results have shown that electrofiltration greatly enhanced the filtration kinetics of aqueous suspensions of anatase [7], quartz sand [8], and kaolin [9]. A similar finding was also obtained in a pilot-scale electrofiltration of SiO 2 using a polyamide membrane with a 0.2-m pore size [10].…”
Section: Introductionsupporting
confidence: 71%
“…It has been reported that a combination of mechanical and electrical filtration (i.e., electrofiltration) can be effective in enhancing membrane flux [6][7][8][9]. In crossflow filtration the bulk flow is tangential to the membrane where there is also a convective flow into the porous surface.…”
Section: Introductionmentioning
confidence: 99%
“…Note that electrolytic ions H 3 O + and OH -may also have a negative effect on the electroosmotic flow (equations A2 and C1), especially in clays. For instance, if a DC electric field is applied, H 3 O + ions accumulate in the filter cake with the anode side becoming acid and OH -ions at the cathode side becoming basic (Larue and Vorobiev, 2004). In acidic conditions, the adsorption of H 3 O + on usually negatively charged particles (clays) make │ζ│ collapse, thus the electroosmotic drainage will cease in the cake at the anode side.…”
Section: Electrolysis Reactions At Electrodesmentioning
confidence: 99%
“…They noted a non-uniform distribution of water content, pH, porosity, electric field intensity and particles zeta potential throughout the mixture. The electrolysis reactions at the electrodes account for this behaviour (Larue and Vorobiev, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to biopolymer suspensions many research groups investigated dead-end electrofiltration of mineral suspensions [49,66,73,75,92,109,114].…”
Section: The Technology Of Electrofiltrationmentioning
confidence: 99%